Sistem Pendukung Keputusan Pemilihan Back Office Terbaik Dengan Menggunakan Metode MOOSRA - Sihotang, Dahner Ismanda Bertenius; Utomo, Dito Putro (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2024)
Choosing the best back office is very important to support increased efficiency and effectiveness in bank operations. At PT. Bank Sumut selects the best employees in the Back Office every year. However, the selection process still has obstacles/problems. The problems faced are that the assessment and input of values is still done manually so it is less professional and quite time consuming due to the large number of back office staff who have to be assessed. Therefore, the final results obtained from the back office selection process are still less than objective. So a system is needed as a reference for the best back office selection process, namely a Decision Support System. A Decision Support System is a system that can provide problem solving capabilities and communication capabilities for problems with semi-structured conditions and unstructured situations. By using the MOOSRA method in the selection process because the MOOSRA method can calculate the weighting of the criteria and can obtain the highest criteria value so that it gets the highest weight to achieve a final ranking. The MOOSRA method is a method in a Decision Support System that can carry out a multi-criteria decision making process and can handle subjective evaluations from information collected from expert groups. The results of data processing carried out using the MOOSRA method can produce the highest final value compared to other alternatives, namely Alternative 1 (A1) with a final value of 0.3733 and is declared worthy of being the best back office.